Reallocation of nitrogen and biomass to the seeds in wheat inoculated with Azospirillum bacteria - Didonet, Agostinho Dirceu; Lima, Osvaldo dos Santos; Candaten, André Alessandro; Rodrigues, Osmar (Pesquisa Agropecuaria Brasileira, 2000)
The effect of inoculating wheat (Triticum aestivum L.) seeds, cultivar Embrapa 16, with powder peat inoculant containing Azospirillum bacteria on yield and remobilization of nitrogen and biomass was studied under field conditions. The strain of Azospirillum brasilense 245 and the isolate 10 of Azospirillum lipoferum were used as inoculants. Different rates of nitrogen were applied at varying stages of plant growth for each inoculated and non-inoculated treatment, distributed in blocks at random with split plots. The accumulation of dry matter and total nitrogen in plant parts was evaluated at anthesis and physiological maturity stages. Harvest index for biomass and N, main yield components, and total N content in the seeds, in addition to yield, were also evaluated at harvest. The preliminary results showed that, even without inoculation effect on yield, there was a better allocation of nitrogen and biomass to the seeds, resulting in heavier seeds, with a lower amount of nitrogen remaining in the straw at physiological maturity. Such effects resulted from a lower number of spikes m-2, probably due to the death of tillers, determining a greater availability of N and biomass to the remaining spikes and seeds.